Green synthesis of benzimidazole derivatives under ultrasound irradiation using Cu-Schiff base complexes embedded over MCM-41 as efficient and reusable catalysts. Issue 4 (16th February 2020) - Bharathi, M.; Indira, S.; Vinoth, G.; Mahalakshmi, T.; Induja, E.; Shanmuga Bharathi, K.
Abstract: We have synthesized two recoverable catalysts by covalently attaching complexes such as Cu-complex-phen and Cu-complex-bipy on MCM-41 through a greener synthetic route. FT-IR, EDX, SEM and TEM microscopy, XRD analysis, N2 adsorption and desorption, ICP-OES and TGA were used to characterize the heterogeneous catalysts. The catalytic functioning of Cu-complex-phen-MCM-41 (C1 ) and Cu-complex-bipy-MCM-41 (C2 ) were shown yield up to 95% for the synthesis of benzimidazole derivatives in ethanol/methanol solvent under ultrasonic irradiation within 90 min. The catalyst was easily recovered and reused up to three times without significant loss of its activity. Graphical Abstract: